2021
DOI: 10.3390/educsci11010015
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Theories of Parenting and the Development of Emotion Understanding in Preschoolers

Abstract: Emotion understanding develops intensively in preschool and junior school. Although the parent/family environment has been shown to affect the development of emotion understanding in children, very little research has examined examined how parents’ view upbringing and education and how they are related to their child’s emotion understanding, given that the intuitive theories of parenting are reflected in actual parent behavior. This study fills this gap in the literature and examines the links between children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Regarding research approaches, it was found that 69.2 % (n=36) used the qualitative type, 26.9 % (n=14) corresponded to quantitative studies, and 3. A high percentage of investigations used samples of 106-307 subjects from 0 to 6 years of age, among which the following stand out: i) surveys of 171 Russian children from 5 to 6 years of age with their respective parents to analyze the theories of parenthood and the understanding of children's emotions (27); ii) evaluation of a diagnostic test on child development in which 224 Colombian children from 2 months to 5 years of age participated together with their parents (28); analysis of emotional competencies and comparison of the influence of the child's sex on the emotional development of 123 Spanish children (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding research approaches, it was found that 69.2 % (n=36) used the qualitative type, 26.9 % (n=14) corresponded to quantitative studies, and 3. A high percentage of investigations used samples of 106-307 subjects from 0 to 6 years of age, among which the following stand out: i) surveys of 171 Russian children from 5 to 6 years of age with their respective parents to analyze the theories of parenthood and the understanding of children's emotions (27); ii) evaluation of a diagnostic test on child development in which 224 Colombian children from 2 months to 5 years of age participated together with their parents (28); analysis of emotional competencies and comparison of the influence of the child's sex on the emotional development of 123 Spanish children (29).…”
Section: Resultsmentioning
confidence: 99%
“…Bisquerra et al (8) state that the family context is the ideal space for the development of emotional competencies. And the family sociodemographic conditions, the educational level, and the economic income of the parents indicate unfavorable actions for the development of children (9). Therefore, it is essential to rethink the importance of the family and the influence of emotional development in early childhood education.…”
Section: Introductionmentioning
confidence: 99%
“…Early childhood is a period of discovery, and the preferences, aptitudes, and interests formed during this period may change over time. The most important attributes and competencies for overall child development were the ability to recognize one's own emotions (Bukhalenkova et al, 2021), to form one's attitude, to build one's character, to develop one's personality, and to learn competence that could form one's identity and be used in a variety of situations. Essentially, transferable, and soft skills like teamwork, communication, achievement accumulation, task management, integrity, fairness, ethics, etc., could be taught from early childhood (Monkeviciene et al, 2020) The Thai national education policy has provided opportunities for the development of children and youth by giving them room to enjoy the freedom of thought and free play, and by creating various opportunities for them to study.…”
Section: Discussionmentioning
confidence: 99%
“…Опросник на выявление интуитивных теорий воспитания в целом пока не прошел проверку валидности, также, как и на российской выборке (Бухаленкова и др., 2021; Bukhalenkova et al, 2021). При этом результаты проверки внутренней надежности по шкалам в исследованиях на российских и азербайджанских мамах очень схожи.…”
Section: обсуждение результатовunclassified